Theoretical study of N-heterocyclic carbenes-catalyzed cascade annulation of benzodienones and enals - Sun, Hui (2013)
Growing attention in developing new N-heterocyclic carbene (NHC)-mediated reactions involving homoenolate intermediates has prompted our interest in exploring the mechanistic details of the related reactions. In this work, we carried out a detailed theoretical study for the NHC-catalyzed annulation reaction of cinnamaldehyde (A) and benzodi(enone) (B) in the presence of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU). By performing density functional theory calculations, we show clearly the detailed reaction mechanism and rationalize the experimental observation. The reaction of A and B falls into two stages: the formation of homoenolate intermediate and the annulation of homoenolate with B. In the homoenolate formation stage, three possible paths are characterized. The pathway involving the DBU-assisted 1,2-proton transfer with a stepwise mechanism is kinetically more favorable, and the DBU-assisted C1 proton departure is the rate-determining step of the total reaction. The annulation of homoenolate with B involves four elementary steps. The conformational difference of homoenolate (cis and trans) leads to two slightly different reaction processes. In the total reaction, the process involving cis-conformation of A is kinetically more feasible. This can be clearly understood through the frontier molecular orbital analysis and the electronic inductive effect. The calculated results are expected to offer valuable information for further design and development of NHC-mediated reactions.